Impact of drought on gas exchange and yield parameters in roselle (Hibiscus sabdariffa L.) - Narejo, Mehar-un-Nisa; Megat Wahab, Puteri Edaroyati; Hassan, Siti Aishah; Che Mohd Zain, Che Radziah (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Effect of drought stress on gas exchange and yield parameters in roselle (Hibiscus sabdariffa L.) was investigated under pot culture conditions in rainout shelter. Experiment was laid out in a randomized complete block design with five replications and three treatments viz, 100%, 67% and 33% field capacity. As the stress increased, reduction in photosynthesis rate, stomatal conductance, intercellular CO2 concentration and transpiration were observed. The number of fruits, fruits weight and calyx yield per plant were not significantly different at 100% and 67% field capacity. These findings suggested that optimum calyx yield can be obtained at 67% field capacity.